Effects of Yinchenhao Tang and related decoctions on DMN-induced cirrhosis/fibrosis in rats - Liu Chenghai; Chen Gaofeng; Wang Gaoqiang; Wang Lei; Sun Mingyu; Liu Cheng; Liu Ping (BMC, 2008)
Abstract Background Chinese medicine decoctions such as Yinchenhao Tang (YCHT), Xiayuxue Tang (XYXT), Huangqi Tang (HQT), Yiguan Jian (YGJ) and Xiaochaihu Tang (XCHT)) were used to treat liver cirrhosis. The present study evaluates the effects of these decoctions on fibrosis in rats induced by dimethylnitrosamine (DMN). Methods DMN solution (0.5%) was injected to rats for three consecutive days per week for four weeks. At the beginning of week 3, rats were randomly divided into 4-week DMN control group, YCHT, XYXT, HQT, YGJ, XCHT and vehicle groups. Each group was orally administered with specific decoctions daily for two weeks. Rats in the vehicle group were orally administered with only water. Results Liver fibrosis and cirrhosis were observed in weeks 2 and 4 in DMN-intoxicated rats. Compared with normal rats, alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) activities and level of total bilirubin acid (TBA) in serum and content of Hydroxyproline (Hyp) in liver tissue of model group rats rose significantly. However, the albumin (Alb) level in serum decreased significantly. Compared with the 4-week DMN group, the pathological conditions and functions of the liver in the YCHT group improved significantly, and the content of Hyp decreased remarkably: only one rat in this group developed liver cirrhosis and the ratio of cirrhosis was only 8.3%. On the other hand, the other decoctions did not show remarkable effects. YCHT inhibited α-SMA activation, including its gene expression into mRNA and protein. Conclusion Among the five Chinese medicine decoctions, YCHT exerted the most significant therapeutic effects on DMN-induced cirrhosis/fibrosis in rats.